Relationship between Health Service Quality and BPJS Patient Satisfaction - La Ede, Abdul Rahman; Budhiana, Johan; Maulana Suryadi, Ashari (Jurnal Health Society, 2024)
Introduction: Patient satisfaction is a response or response given by the patient after comparing expectations with what the patient experiences or gets for the quality of service provided. The quality of health services has a direct impact on the level of patient satisfaction. The purpose of this study was to determine the relationship between the quality of health services and BPJS patient satisfaction at the UPTD Puskesmas Kadudampit, Sukabumi Regency. Methods: This type of research uses correlational research with a cross sectional approach. The population in this study were all patients who used BPJS health services at the UPTD Puskesmas Kadudampit, Sukabumi Regency with a sample of 320 people using accidental sampling and proportional random sampling techniques. Data collection techniques using questionnaires. Univariate data analysis using frequency distribution and bivariate analysis using somers’ D test. Result: The results showed that there was a relationship between the quality of health services and BPJS patient satisfaction with a p-value of 0.000. Conclusions: There is a relationship between the quality of health services and BPJS patient satisfaction.